Synthesis of Microsheets Bi4Ti3O12 and Bi4Ti2.95V0.05O12 via Molten NaCl-KCl Salt Method - Anton Prasetyo; Andy Nur Muhammad Guntur; Suci Noerfaiqotul Himmah; Nur Aini; Usman Ali Rouf; Abdul Aziz (The Journal of Pure and Applied Chemistry Research, 2022)
Bi4Ti3O12 is a tri-layer Aurivillius member compound that was reported to have good photocatalytic properties. Metal element doping and morphological particle tuning are strategies to increase photocatalyst activity. In this research, the compound micro sheets Bi4Ti3O12 and Bi4Ti2.95V0.05O12 were synthesized using molten NaCl/KCl salt. The diffractogram shows that the Bi4Ti3O12 sample was successfully synthesized, however, there are still found impurities at the Bi4Ti2.95V0.05O12 sample. Micrographs showed that the morphology particle samples is. The results of UV-Vis DRS spectra calculation show that both samples have a band gap energy of ~2.97 eV.